Oncolytic Virotherapy for Cancer: Clinical Experience - Chaurasiya, Shyambabu (Biomedicines, 2021)
Oncolytic viruses are a new class of therapeutics which are largely in the experimental stage, with just one virus approved by the FDA thus far. While the concept of oncolytic virotherapy is not new, advancements in the fields of molecular biology and virology have renewed the interest in using viruses as oncolytic agents. Backed by robust preclinical data, many oncolytic viruses have entered clinical trials. Oncolytic viruses that have completed some levels of clinical trials or are currently undergoing clinical trials are mostly genetically engineered viruses, with the exception of some RNA viruses. Reolysin, an unmodified RNA virus is clinically the most advanced oncolytic RNA virus that has completed different phases of clinical trials. Other oncolytic viruses that have been studied in clinical trials are mostly DNA viruses that belong to one of the three families: herpesviridae, poxviridae or adenoviridae. In this review work we discuss recent clinical studies with oncolytic viruses, especially herpesvirus, poxvirus, adenovirus and reovirus. In summary, the oncolytic viruses tested so far are well tolerated, even in immune-suppressed patients. For most oncolytic viruses, mild and acceptable toxicities are seen at the currently defined highest feasible doses. However, anti-tumor efficacies of oncolytic viruses have been modest, especially when used as monotherapy. Therefore, the potency of oncolytic viruses needs to be enhanced for more oncolytic viruses to hit the clinic. Aiming to achieve higher therapeutic benefits, oncolytic viruses are currently being studied in combination with other therapies. Here we discuss the currently available clinical data on oncolytic viruses, either as monotherapy or in combination with other treatments.